2017
DOI: 10.3389/fnins.2017.00551
|View full text |Cite
|
Sign up to set email alerts
|

Head Stabilization in the Pigeon: Role of Vision to Correct for Translational and Rotational Disturbances

Abstract: Stabilization of the head in animals with limited capacity to move their eyes is key to maintain a stable image on the retina. In many birds, including pigeons, a prominent example for the important role of head stabilization is the characteristic head-bobbing behavior observed during walking. Multimodal sensory feedback from the eyes, the vestibular system and proprioceptors in body and neck is required to control head stabilization. Here, we trained unrestrained pigeons (Columba livia) to stand on a perch th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Indeed, both the vestibulocollic and the cervicocollic reflex-which remained functional in the dark-underpin active head stabilization in vertebrates (6,14). These findings are consistent with reports that body-fixed pigeons (15), free-standing pigeons (16), and hand-held owls (17) stabilize their head in the dark based on vestibular and proprioceptive feedback alone.…”
Section: Significancesupporting
confidence: 87%
“…Indeed, both the vestibulocollic and the cervicocollic reflex-which remained functional in the dark-underpin active head stabilization in vertebrates (6,14). These findings are consistent with reports that body-fixed pigeons (15), free-standing pigeons (16), and hand-held owls (17) stabilize their head in the dark based on vestibular and proprioceptive feedback alone.…”
Section: Significancesupporting
confidence: 87%
“…Owing to the fact that the beak disappeared from the videos during most vertical foraging movement of the pigeons, it was not possible to track their beak, which might have provided direct information about head orientation. However, Theunissen and Troje (2017) demonstrated that pigeons often take a stable body position and compensate for the movement of environmental cues with head rotations. In the absence of moving cues, they usually keep their head-body position aligned.…”
Section: Discussionmentioning
confidence: 99%
“…Another technique, and the one that we will adopt here, is to use a well-calibrated motion-capture system that can record the 3D coordinates of small re ective markers attached to a bird's head at a high temporal frequency and with submillimeter precision. Previous studies have employed this method to study pigeons' visual perception and 3D head orientations during perching (head stabilization) 41 , pecking (beak control) 42 , and walking (head bobbing) 43 . However, its use has been limited to relatively small laboratory spaces and the analysis of these relatively small-scaled individual behaviors.…”
Section: Introductionmentioning
confidence: 99%